PENGARUH MODEL PEMBELAJARAN OUTCOME-BASED EDUCATION DALAM KURIKULUM MERDEKA TERHADAP PENGEMBANGAN KREATIVITAS SISWA SD KELAS VI PADA PELAJARAN BAHASA INDONESIA - Citrawati, Tyasmiarni (Tarbawi : Jurnal Pendidikan Islam, 2024)
This research aims to analyze the influence of the Outcome-Based Education (OBE) model in the "Kurikulum Merdeka" (Freedom Curriculum) on the development of creativity among fourth-grade students in Indonesian language lessons. The research employed a quantitative method with a quasi-experimental design. The study sample consisted of fourth-grade students from 10 elementary schools in Bangkalan Regency selected randomly. Data collection involved creativity tests and observations. Data analysis used statistical tests to compare the differences between the experimental group using the OBE model and the control group using conventional methods. The results indicated a significant increase in the creativity levels of students who underwent OBE-based learning compared to those using conventional methods. Students taught with the OBE model showed higher creative thinking abilities, particularly in idea generation, flexibility, and originality. The conclusion drawn from this research is that the Outcome-Based Education model within the Kurikulum Merdeka positively impacts the development of creativity among fourth-grade students in Indonesian language lessons. The implementation of the OBE model can be an effective strategy to foster student creativity at the elementary school level. These findings align with the research objective of enhancing student creativity through a learning approach focused on outcomes.